Performance Comparison of 7-level Multi-Level Inverter Topologies using FPGA - Nithya, R.; Anitha, T.; Arulaalan, M. (International Journal of Membrane Science and Technology, 2023)
This paper compares the Multi-Level Inverter namely Switched Ladder and H-Bridge Topologies for the performance parameters. The topologies considered are fed with the switch patterns from the non-carrier angle manipulated formula. The switching angle algorithm identifies on which particular angle the signal has to be generated. It is identified based on four algorithm namely half height method, equal phase method,This paper concentrates on the 7-level MLI AC output using the synthesizable VHDL code and implemented using the FPGA in real-time. For verification in simulation, the cross-compiling is attained using the System Generator tool.